(untitled) (The Peerian Journal, 2025)
The article deals with the category of conditionality in linguistics as a system of syntactic and semantic means expressing the conditionality between events. Conditional relations are analyzed at different levels of syntactic structure: from prepositional and case forms and simple sentences to complex syntactic constructions. Special attention is paid to the functional-semantic field of conditionality, in the center of which are compound sentences with conditionals, as well as its peripheral elements. The distinction between potential and irreal condition is substantiated, semantic nuances arising from the weakening of conditional meaning, including convergence with causal and concessive relations, are revealed. It is shown that the condition can express not only action, but also state, and that the category of condition covers a wide range of syntactic units designed according to grammatical laws and possessing a sign nature